Knowledge on Post-Exposure Prophylaxis of Hepatitis B Among Undergraduate Nursing Students - Mandal, Reena; Acharya, Shusma; Karki, Aayushma (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Post exposure prophylaxis (PEP) is a treatment that can be used after possible exposure to the hepatitis B virus through sex, drug injecting equipment or injury such as needle stick injury. Post-exposure prophylaxis can help prevent hepatitis B to many health care workers after being exposed to hepatitis virus. Due to the frequent contact with patients’ blood, bodily fluids, needles, nurses are more susceptible to contact with HBV infection. The overall objective of the research was to assess the knowledge on post exposure prophylaxis of hepatitis B among undergraduate nursing students. Method: A descriptive cross-sectional study was carried out among 148 nursing students in Manmohan Memorial Institute of Health Sciences using probability proportionate stratified random sampling technique. Ethical approval was taken from the Institutional Review Committee (IRC) of Manmohan Memorial Institute of Health Sciences, MMIHS. Informed consent was taken from the study participants. Data was collected using self-developed structured questionnaire from Jestha 20 to 32, 2081 (2024 June 2nd to 2024 June 14). The collected data was analyzed in SPSS version 23.0 using descriptive statistics and inferential statistics chi-square test was done to explore the association between variables and interpretation was done. Results: Out of 148 respondents, more than half(52.7%) had adequate level of knowledge on meaning of PEP(85.85), common constituents of Hepatitis B PEP(77.7%),indication of PEP (72.3%), meaning of Hepatitis B Immunoglobulin (HBIG) (68.2%), route of HBIG(71.6%). But there was inadequate level of knowledge on efficacy of PEP(23.0%), types of exposure(12.2%), adequate value of HBsAg titre (10.8%), standard PEP for positive source patient and vaccinated exposed person with inadequate HBsAg titre (9.5%). There was statistically significant association between academic year (p=0.001), vaccination status(p=0.025) with level of knowledge on PEP. Conclusion: About half of the respondents have inadequate knowledge on PEP of Hepatitis B, there is gap in knowledge on standard protocol of PEP. Therefore, nursing students should be updated on PEP by revising curriculum.